Efek Visual Motor Ability Enhancement Program (VMAEP) terhadap Visual Motor Integration (VMI), Visual Perception (VP), dan Motor Cordination (MC) pada Anak Berkebutuhan Khusus - Roh Hastuti Prasetyaningsih; Erayanti Saloko (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Inclusive education in Indonesia continues to face challenges, particularly in meeting the needs of children with special needs. Evidence indicates that difficulties in visual–motor integration (VMI), visual perception (VP), and motor coordination (MC) are closely associated with poor academic performance in reading, writing, and mathematics. Activity-based visual–motor interventions have shown promising outcomes. Objectives: Therefore, this study examines the effectiveness of the Visual Motor Ability Enhancement Program (VMAEP) in improving VMI, VP, and MC among children with special needs. Methods: This research employed a pre-experimental design with a pre test–post test approach. The study sample consisted of 20 children with special needs at Kamila GIS Lazuardi, recruited using a constitutive sampling technique. All participants received the VMAEP intervention and were assessed using the Beery VMI (Beery–Buktenica Developmental Test of Visual–Motor Integration). Measurements were conducted twice, before and after the intervention. Results: A total of 20 children aged 4–14 years participated in this study. The mean VMI score changed by 0.43, while visual perception (VP) increased by 5.78 and motor coordination (MC) improved by 3.79. All p-values were < 0.05, indicating statistically significant effects. Cohen’s d analysis demonstrated a small-to-moderate effect on VMI (0.41), a large effect on VP (1.05), and a very large effect on MC (1.59). Conclusion: The findings indicated not only significant effects of VMAEP on VMI, VP, and MC among children with special needs, but also clinically meaningful effect sizes. Keywords: Visual Motor Ability Enhacement Program (VMAEP), Visual Motor Integration, Anak Berkebutuhan Khusus (ABK).